Remarkable magnetostructural coupling around the magnetic transition in CeCo0.85Fe0.15Si - Correa, V.F. (2016)
Fil: Correa, V.F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina